DEVELOPMENT OF PAMUSI ONLINE GAME MEDIA OF GREATEST COMMON DIVISOR AND LEAST COMMON MULTIPLE IN ELEMENTARY SCHOOL - Quriana, Intan Maulida; Murti, Rahayu Condro; Bayan, Umar (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The research started from the problem of online learning which requires learning media to motivate students to increase their interest in learning. Researchers developed mathematics learning media based on the online game PAMUSI on the material Lowest Common Multiple (LCM) and Greatest Common Factor (GCF). This research aims to find out the influence and feasibility of the PAMUSI online game media on GCF and LCM material in class IV at Tegalpanggung Elementary School. The research method uses Research and Development (RnD) with the ADDIE development model. The stages in this research include analysis, design, development, implementation and evaluation. The subjects of this research were fourth grade students at Tegalpanggung Elementary School. Data collection techniques use interviews, observation, and literature study. The analysis used is qualitative descriptive analysis. The results of the validator research showed that the PAMUSI online game learning media was suitable for use to increase interest in learning. The results of material validation obtained an average score of 4.3 in the